Studi Model Pembelajaran Problem Solving Terhadap Motivasi Belajar Matematika - Arnius Laoli; Amin Otoni Harefa (Jurnal Tunas Pendidikan, 2023)
This research is based on a preliminary study conducted by researchers, found problems, namely (1) Mathematics is often considered a difficult subject to understand (2) Mathematics is a subject that is considered the most difficult, most boring and often considered the most difficult subject. scary and (3) the number of complaints from students about math lessons that are difficult, uninteresting and boring. study aims to describe the study of problem solving learning models on the motivation to learn mathematics whether or not it can improve mathematics learning outcomes. This type of research is library research (Library Research). Widiasworo, (2018:30) said "Library research methods are included in one type of research method based on the place of research. Based on the results of this study, the researcher suggests that in the learning process, the study of problem solving learning models should be used on the motivation to learn mathematics so that student learning outcomes can increase.